A new model of resource planning for optimal project scheduling - Valuev, Andrey (Mathematical Modelling and Analysis, 2007)
It is well known that not only the classical model of PERT/CPM but its later improvements treat a resource planning in the project scheduling in a very limited way. Using them it is possible to calculate the optimum amount of resources taken from outside or financial expenses for separate operations but it is quite impossible to share internal resources between parallel operations. Instead of these models a new one is introduced. It combines relationships concerning sharing resources‐capacities and works dynamics and perhaps other ones that express the use of materials and funds, inventory control and so on. Non‐strict work precedence conditions may be used as well. The model as a whole slightly differs from the model of resource planning in complex industrial systems proposed by the author and retains its general properties, notably the form of optimality conditions. A decomposition method of the project optimum fulfillment is proposed.First Published Online: 14 Oct 2010